Vegetable based diversified farming enhanced farm profitability under sodic environments - Sharma, Raman; Parjapat, Kailash; Sheoran, Parvender; Sanwal, S K; Sharma, P C; Chahal, V P (Indian Farming, 2021)
For enhancing income of reclaimed or marginal sodic lands irrigated with alkali water, vegetable based partial crop diversification module was synthesized at farmer’s field under Farmer FIRST Programme. Out of total 4.5 acres land area, only one acre was converted into vegetable and fodder based diversified cropping systems depending on the farmer’s resource base and family size/ labour availability. Two crop sequences including short duration vegetables in cereal (rice–garden pea–onion) and fodder (sorghum–cauliflower–okra) based cropping systems enhanced productivity and profitability margins with an additional income of ` 1,11,903 and incremental benefit cost ratio of 3.74 for each rupees incurred towards the cultivation of vegetable crops compared to traditional rice-wheat system.